The translation and adaptation of the parent proxy kid-kiddoKINDLR questionnaire on quality of life (QoS) for primary school-aged children with hearing impairment - Wan Ahmad, Wan Aslynn Salwani; Mohamed Zain, Nor Azrita; Kamarul Arifin, Nur Amirah (Penerbit Universiti Putra Malaysia, 2020)
The objectives of this paper are to translate and adapt the parent proxy Kid-KiddoKINDLRR questionnaire on Quality of Life (QoL) for children with hearing impairment into Malay language and to describe the translation techniques used, as well as the equivalence issues, with regards to morphology and semantics, encountered during the process. A combined technique of forward-backward translation was used following the translation protocol provided by KINDL developer. The techniques involved in the translation process were the forward translations by three translators, reconciliation between the translations. Next, this questionnaire was backward translated, and harmonised. As the types of equivalence were determined, several related issues were identified; vocabulary equivalence, idiomatic equivalence and grammatical-syntactical equivalence. However, it can be reported that there were no issues in experiential and conceptual equivalence during the process. The translation of this questionnaire is essential in order to shed light on the children’s QoL in the Malay speaking community.